Effects of a New Maintenance Fluid Containing Sodium Acetate as the Base Component and Electrolytes during Renal Biopsies in Patients with Chronic Glomerulonephritis - Tomino, Yasuhiko; Funabiki, Kazuhiko; Suzuki, Shigenobu; Maeda, Kunimi; Sekizuka, Keiko; Fukui, Mitsumine; Horikoshi, Satoshi (Arzneimittelforschung, 2004)
A new maintenance fluid containing sodium acetate as the base component and electrolytes (Veen® 3G, test preparation) for a maximum of 24 h was infused to 15 patients hospitalized for renal biopsies and requiring intravenous supplements of water, electrolytes and energy because oral or enteric ingestion was inadequate or impossible. A physical examination, blood chemistry tests and urinalysis were performed, and the global improvement rating was obtained by scoring the effects on a) maintenance of cardiovascular hemodynamics (systolic blood pressure), b) blood glucose control (blood glucose level), c) utilization of sugar (free fatty acids, total ketone bodies), d) maintenance of serum electrolytes, e) amount of sugar excreted in the urine and f) maintenance of urinary volume. The results were excellent or good in all of the 15 patients analyzed. The test agent wasnot the direct cause of any adverse events or abnormal changes in laboratory findings, and no safety-related problems were observed in any of the patients. These results indicated that the test preparation used in this study is a clinically useful and highly safe fluid agent.
Keywords: Glomerulonephritis; Maintenance fluid, electrolytes and sodium acetate; Veen® 3G, clinical studies, renal biopsy